UNDERSTANDING THE SOCIAL AND CULTURAL IMPLICATIONS OF MUDIK (HOMECOMING) TRADITION: A MULTI-ETHNIC STUDY IN INDONESIA - Azhari, Teuku; Sahputri, Juwita (Jurnal Sosiologi Dialektika Sosial, 2024)
The Mudik tradition in Indonesia, attracting millions of people annually, involves mass migration from urban areas to hometowns during major holidays. While traditionally a time for family reunions and cultural activities, Mudik is a complex phenomenon with profound implications for Indonesian society, especially among different ethnic groups. This study utilizes qualitative ethnography to explore the social and cultural impact of Mudik in Indonesia. Participants from diverse ethnic backgrounds, such as Javanese, Sundanese, Balinese, and Madurese, provide valuable insights. Findings show that Mudik preserves cultural traditions, strengthens family ties, and promotes group cohesion. However, modernization has led to changes in Mudik gatherings. Nonetheless, it remains a strong link connecting migrant workers with their families, positively influencing social ties and work performance. Additionally, Mudik contributes to the formation of social identity and cultural practices. Respondents' experiences highlight the diversity of Mudik traditions and the need for a nuanced understanding to address stereotypes within Indonesia's cultural landscape. This research sheds light on Mudik's significance for different ethnic groups in Indonesia.